Corrosion and materials selection : a guide for chemical and petroleum industries - Bahadori, Alireza (John Wiley & Sons Ltd, 2014)
The petroleum and chemical industries contain a wide variety of corrosive environments, many of whichare unique to these industries. Oil and gas production operations consume a tremendous amount of ironand steel pipe, tubing, pumps, valves, and sucker rods. Metallic corrosion is costly. However, the cost ofcorrosion is not just financial. Beyond the huge direct outlay of funds to repair or replace corroded structures are the indirect costs ' natural resources, potential hazards, and lost opportunity. Wasting natural resources is a direct contradiction to the growing need for sustainable development. By selecting the correct material and applying proper corrosion protection methods, these costs can bereduced, or even eliminated. This book provides a minimum design requirement for consideration whendesigning systems in order to prevent or control corrosion damage safely and economically, and addresses: Corrosion problems in petroleum and chemical industriesRequirements for corrosion controlChemical control of corrosive environmentsCorrosion inhibitors in refineries and petrochemical plantsMaterials selection and service life of materialsSurface preparation, protection and maintainabilityCorrosion monitoring - plant inspection techniques and laboratory corrosion testing techniques Intended for engineers and industry personnel working in the petroleum and chemical industries, this book is also a valuable resource for research and development teams, safety engineers, corrosion specialists and researchers in chemical engineering, engineering and materials science.
Keywords: Petroleum refineries -- Materials -- Corrosion.; Petroleum pipelines -- Corrosion.; Corrosion and anti-corrosives.; elektronické knihy; electronic books